Genetic divergence, variability in oat - Chaudhary, Mayank; Singh, S K; Singh, S P.; Thenua, O V S (Indian Farming, 2018)
The analysis of genetic divergence through Mahalanobis D2 statistics showed considerable genetic diversity among genotypes. The thirty-eight genotypes were grouped into 8 clusters. The III (8 genotypes), I (7 genotypes) and II (7 genotypes) cluster having the maximum number of genotypes. This envisaged that the genotypes grouped within a particular cluster were more or less genetically similar to each other and apparent wide diversity was mainly due to the remaining genotypes distributed over rest of the other clusters. Per cent contribution and expression of characters towards the genetic divergence play an important role in selecting the superior genotypes among diverse genotypes. Green fodder yield per plant had maximum contribution towards the genetic divergence followed by days to 50% flowering, plant height, dry fodder yield per plant, number of leaves per plant, number of tillers per plant and length of spike. Remaining traits showed very low contribution per cent towards the genetic divergence. Maximum intra-cluster distance was recorded in III indicating greater genetic divergence between the genotypes belongs to these clusters and crosses involving genotypes viz., NDO-1, Kent, OS 7, JHO-2001-1, UPO 272, AOS 1-1, UPO 268 and JHO-2002-6 are suggested. Crosses in the above combinations are expected to provide enough genetic variability to select high green fodder yielding and stable segregates in the segregating generations. Genetic divergence study suggested that crosses between the genotypes of cluster VI (EC-246128), cluster VII (EC-2676176) and genotypes of cluster V (UPO-2005-1, EC-1176404, JHO-851 and EC-246198) for getting better hybrid vigour in F1 or better hybrids and also for good recombinants in segregating population.